Factors affecting entrepreneurial intention levels - Francisco Li\~nán; Juan Carlos Rodríguez-Cohard; José Manuel Rueda-Cantuche (European Regional Science Association (ERSA), 2005)
Entrepreneurship is becoming a very relevant instrument to promote economic growth and development in different regional and national economies. However, social scientists have not still agreed on the determinants of the decision to become an entrepreneur. Therefore, there is some concern that policies may not be sufficiently efficient in achieving this objective. From a psychological point of view, the intention to become an entrepreneur has been described as the single best predictor of actual behaviour (Ajzen, 1991; Kolvereid, 1996). Hence, some studies have started to analyse the entrepreneurial intention and its determinants (Krueger et al., 2000) but however, methodologies and research instruments used so far differ widely. Then, the availability of a validated instrument to measure abilities, attitudes and intentions towards entrepreneurship could be of much help. In this paper, we use an Entrepreneurial Intention Questionnaire (EIQ), which has been recently validated, to measure entrepreneurial intentions in a sample of students from different Spanish universities. After a brief description of the characteristics and psychometric properties of the EIQ, most important results are discussed. In particular, we pay attention to the influence of different personal and family variables on the entrepreneurial intention level. These variables could be considered as belonging to the institutional environment of each territory. Differences in institutions -in a broad sense- may be a very relevant factor to explain divergent entrepreneurial activity levels. Results show how these external variables affect intention and, as a result actual entrepreneurial behaviour.
Keywords: 330